Smartphone-Based Kegel Exercises for Stress Urinary Incontinence: A Systematic Review and Meta-Analysis of RCT - Hakim, Surahman; Djusad, Suskhan; Kadarusman, Adib Kamil Putra; Hadinata, Valencia; Amelia, Safira; Suskhan, Rizki Fauzi; Adriansyah, Putri Nadhira (Fakultas Kedokteran Universitas Andalas, 2026)
Introduction : To evaluate the effectiveness of smartphone-based applications in supervising Kegel exercises for women with Stress Urinary Incontinence (SUI), specifically in improving treatment adherence and reducing symptom severity as measured by the ICIQ-UI-SF score. Method : This study compares smartphone-based applications for supervising Kegel exercise in women with SUI. Article retrieved from 3 databases using specific keywords. ICIQ-UI-SF scores and adherence data is the main outcome in this article. Results : Five RCTs with a total of 475 participants were included. Three studies demonstrated improved adherence among intervention groups using smartphone applications. Meta-analysis revealed that application based supervision resulted in significantly better post-treatment ICIQ-UI-SF Score (SMD: -0.46, CI [-0.65,-0.28], p < 0.00001) Conclusion : Smartphone applications as a supervision tool for SUI patients who underwent Kegel exercise as a conservative treatment is proven to reduce severity and increasing adherence of the therapy.